Evaluation of Implementation Effect of Reform and Practice of Vocational Literacy Curriculum for Higher Vocational Computer Science Majors Based on C4.5 Model - Xu, Ai min; Lv, Yan; Dai, You Jia (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: The cultivation of vocational literacy of higher vocational computer students is related to the employment prospects of graduates and has a significant impact on the computer talent market. The success or failure of curriculum reform will directly impact the effect of cultivating professionalism in higher vocational computer majors.OBJECTIVES: This paper introduces the source and function of the C4.5 model, establishes model evaluation indexes to assess the application effect of the C4.5 model; the number of iterations and prediction accuracy are important indexes of the model's functioning and puts forward five measures suggestions for the reform of vocational literacy course of higher vocational computer majors.METHODS: C4.5 model is applied to reform vocational literacy courses for higher vocational computer majors, and the effect of practical implementation is evaluated using a questionnaire.RESULTS: By applying the C4.5 model to reform the vocational literacy course for senior computer majors, the graduates' vocational literacy has been significantly improved.CONCLUSION: The research contributes to the realization of the goal of cultivating higher vocational computer talents and provides the market with computer talents with outstanding professionalism.
Keywords: vocational literacy; curriculum reform; C4.5 model; higher vocational computer science majors